Peran Kepuasan Kerja dalam Memediasi Pemberdayaan terhadap Kinerja Karyawan pada Hotel Bali Summer - Rahayu, Putu Desyana; Sudibia, Gede Adnyana (E-Jurnal Manajemen, 2014)
Performance is one of the critical success factors of the company. The purpose of this study was to determine the role of job satisfaction in the performance of employee empowerment mediate the Bali Summer Hotel. Two factor theory states that there are hygiene factors and motivators related to the achievement of corporate goals. Job satisfaction encourage employees to improve their performance, whereas human resources aspect can be improved through empowerment. This study took place at the Hotel Bali Summer. This research is conducted because during the time happened by the height mount of the employee turnover rate that gives rise to a sense of dissatisfaction that employee performance decreases. Data collected by distributing questionnaires to the employees of the hotel as a number of respondents 43 respondents. Engineering analysis using path analysis. Indicated also by the results of research that empowerment variable positive and significant effect on job satisfaction. Empowerment also has a positive and significant influence on employee performance. Neither variable job satisfaction has a positive and significant influence on employee performance. Variable able to mediate the effect of job satisfaction among variables of empowerment on employee performance in Hotel Bali Summer. Keywords: employee performance, job satisfaction and empowerment